Handball-specific loading acutely reduces the acromiohumeral distance in experienced handball players and in non-handball experienced athletes - Rentz, Carolin; Legerlotz, Kirsten (Frontiers in Sports and Active Living, 2022)
Context: When playing handball, the preservation of the subacromial space, which can be quantified by the acromiohumeral distance (AHD), plays a crucial role for shoulder health of handball players. Acute effects of handball-specific loading on the subacromial space with consideration of individual adaptions resulting from long-term handball-specific loading experience have yet to be determined. Objective: To (1) assess the acute effects of handball-specific loading on the AHD in healthy experienced handball players (HB) and non-handball experienced athletes (CG) and (2) to assess the AHD behavior in relation to individual intrinsic factors to identify possible risk factors and the effect of handball-specific experience associated adaptations. Participants: 20 HB (10m;10w) and 20 CG (10m;10w); 24±5years Intervention: Handball-specific loading protocol Main Outcome Measures: The AHD was measured by ultrasonography at 0° and 60° abduction pre and post intervention. Isometric shoulder strength was measured with hand-held dynamometry. Shoulder range of motion was measured with goniometry. Results: Handball-specific loading led to significantly reduced AHD in the dominant shoulder in the 60° abducted position in both groups (HB: –1.7±2.0mm; CG: –1.1±2.0mm) and in the non-dominant shoulder in 0° (–0.7±1.5mm) and 60° abducted position (–1.3±1.8mm) in HB only. Handball-specific loading enhanced AHD reduction when elevating the shoulder from 0° to 60° in both groups and arms. Larger shoulder abduction strength affected the maintenance of the AHD positively. HB demonstrated less shoulder strength compared to CG. Conclusions: Handball-specific loading can affect the ability to preserve the subacromial space which might put handball players at risk for shoulder injuries. Poor shoulder strength can aggravate this mechanism. Therefore, implementation of strengthening exercises of the external rotator and abductor muscles in the training schedule may improve shoulder health of handball players.